Beta Glucans - Mechanisms of Action - Vetvicka, Vaclav; Novak, Miroslav (Bentham Science Publishers, 2011)
β-Glucan is generally considered to be a very safe immunomodulator. It is a well-known biological response modifier (BRM) that has been used as an adjuvant therapy for cancer since 1980, mostly in Japan. β-Glucan enhances the innate host defense against certain bacteria, yeast, and viral pathogens. I addition, glucans are also considered to be important in prophylaxis against irradiation. Various types of glucans are now routinely added both to human and animal food. At least 26 clinical trials are currently under way in several countries. The authors of this ebook have selected and brought together information on both theoretical and practical aspects of β-glucan use. The book is suitable for readers seeking timely and precise information on β-glucan history and various biological effects including possible use in the treatment of various diseases, without having any preliminary knowledge of natural immunomodulators. The book should not only provide an inspiration for carbohydrate and clinical chemists for further investigations in biomedicine, but it also presents a number of practical applicable results in immunology